Qualidade da carne de borregos Morada Nova submetidos a diferentes dietas de terminação - Barroso, Marina Rose Campos (2022)
This study aimed to evaluate the quality of Morada Nova lamb meat submitted to two finishing diets without and with 15% reductions in crude protein (CP) and total digestible nutrients (TDN). Sixteen non-castrated male lambs of the Morada Nova breed, weighing 19.04 2.94 kg and 160 days of age were used, allocated in collective bays using GrowSafe Systems® automated feeders. The diets were formulated without reduction (0%) and with a 15% reduction of nutrients (CP and TDN), for growing lambs, with an average daily weight gain of 200 grams/animal, with the use of high-concentrate diets (HCD) pelletized. The roughage: concentration ratio of 18:82 and 43:57, respectively, were adopted. The physical-chemical analysis performed on the Longissimus dorsi muscle was centesimal composition, pH, color (L*, a* and b*), water holding capacity, cooking loss, shear force, lipid and cholesterol levels, and fatty acid profile. The data were submitted for analysis of variance to be compared by the F test at 5% probability using the statistical program SAS®. There were no differences between the diets for the evaluated parameters, except for fatty acids C17:0 and C17:1 (P<0,05). Therefore, finishing Morada Nova lambs with a 15% reduction in crude protein and total digestible nutrients does not compromise meat quality, allowing meat of acceptable quality. Furthermore, it is recommended to adopt the diet with a 15% reduction proposed by the NRC (2007) for locally adapted animals from the semiarid region of the Morada Nova breed.